(untitled) (Swiss Medical Weekly, 2019)
Carotid ultrasound allows rapid and reliable quantification of atherosclerosis in humans. Although the definition of carotid plaque is not uniform, intimal thickening of at least 1.5 mm is currently defined as plaque. Plaque can be easily quantified by tracing the plaque area, a software-independent low-cost technique. More sophisticated quantifications involve 3D volume acquisitions, which is software-dependent and not widely available. Carotid plaque has a higher prognostic impact than intimal thickening, and carotid plaque volume showed comparable prognostic power to coronary calcifications. According to the latest European Joint ESC guidelines, carotid artery scanning should be considered for adjusting the level of risk especially in intermediate-risk subjects. There are various methods to incorporate results from imaging into clinical decision making, such as using arterial age instead of chronological age in risk equations or post-test risk calculations using the sensitivity and the specificity of the results from a given carotid plaque burden. In subjects with low or intermediate cardiovascular risk, the search for atherosclerosis may be appropriate and ultrasound of the carotid or the femoral arteries could be the primary method applied (depending on local expertise). Assessment of carotid total plaque presence, progression, stability and regression over time may be a valuable clinical tool for optimising the intensity of preventive therapies.